Sistema Informático de gestión documental para la Facultad de Ciencias Administrativas. - Oña Iza, Carmen Alexandra (2018)
In the Faculty of Administrative Sciences of the Technical University of Cotopaxi, it was evidenced that the documents were physically stored and there is excessive documentation, all this led to the loss of time, in addition they forgot the corresponding procedures and several of the times they went beyond the established dates, for this reason the present project was carried out in order to facilitate the documentary management as a technological support tool. As a solution, a web application has been developed that facilitates document management, within which aspects such as: department management, user management, management of document types, document management, management of reminders, sending documents, completing the process and consult documents. To achieve the aforementioned, a bibliographical research has been carried out, compiling information related to similar investigations, definitions about document management, which provided a deep knowledge about the object of study, also a field investigation which allowed to know thoroughly the problem raised based on everything required by the faculty. For the development of the application the SCRUM methodology was used, the development tools such as Visual Studio 2015 and database in SQL Server 2012.